Holistic Approach to Tackle (micro)Plastic Pollution: The Case of Mauritius (Global Journal of Science Frontier Research, 2023)
There has been a drastic increase in the production and use of plastics today Society has benefitted largely from the advent of plastics They play a major role in our economic and social development encompassing every sector from health and food preservation through to transportation and enhancing the digital age Plastics have a life expectancy of many years before getting degraded or fragmented into microplastics or nano-plastics which are easily ingested by aquatic species and eventually end-up in humans The marine ecosystems and health of human population are severely impacted upon due to release of harmful chemicals from the latter Moreover since the movement of plastic wastes has no boundaries plastic pollution is considered to a major threat to our planet Countries around the world are having recourse to policy measures and economic instruments to counteract plastic pollution Likewise the Republic of Mauritius with the main island in the south-west of the Indian Ocean is not spared from the adverse effects of plastic pollution
Keywords: circular economy; recycling technologies; life cycle assessment; governance of plastic waste; Mauritius